1-(8a-3)²=1-(64а²-48а+9)=1-64а²+48а-9=-64а²+48а+(1-9)=-64а²+48а-8=-8(x-0,25)(x-0,5)=-(8х-2)(8х-4)=(2-8х)(8х-4) Для того чтобы разложить на множители нужно приравнять данное выражение к нулю -64а²+48а-8=0 Cчитаем дискриминант: Дискриминант положительный
1-(8a-3)²=1-(64а²-48а+9)=1-64а²+48а-9=-64а²+48а+(1-9)=-64а²+48а-8=-8(x-0,25)(x-0,5)=-(8х-2)(8х-4)=(2-8х)(8х-4)
![D=48^{2}-4\cdot(-64)\cdot(-8)=2304-2048=256](/tpl/images/0031/8424/6cc1f.png)
![\sqrt{D}=16](/tpl/images/0031/8424/827ac.png)
![x_{1}=\frac{-48+16}{2\cdot(-64)}=\frac{-32}{-128}=\frac{1}{4}=0,25](/tpl/images/0031/8424/0e2dc.png)
![x_{2}=\frac{-48-16}{2\cdot(-64)}=\frac{-64}{-128}=\frac{1}{2}=0,5](/tpl/images/0031/8424/a23da.png)
Для того чтобы разложить на множители нужно приравнять данное выражение к нулю
-64а²+48а-8=0
Cчитаем дискриминант:
Дискриминант положительный
2) a⁵+a⁴-2a³-2a²+a+1=а⁴(а+1)-2а²(а+1)+(а+1)=(а⁴-2а²+1)(а+1)=(а+1)(а²-1)²